Association between Rash and a Positive Drug Response Associated with Vinorelbine in a Patient with Primary Peritoneal Carcinoma - Mustafa M. Mohammad; Kostas N. Syrigos; M. Wasif Saif (Case Reports in Dermatological Medicine)
Vinorelbine (Navelbine, VRL) is commonly used for platinum-resistant ovarian cancer and has been shown to be effective in patients with recurrent primary peritoneal carcinoma. Of VRL’s major side effects, skin rash is uncommon, and, if it does occur, it is usually localized to site of injection. In this case report, a 71-year-old Hispanic female with primary peritoneal carcinoma received single agent VRL as fourth-line regimen, which she tolerated very well except for a skin rash related to VRL. The rash continued to progress throughout 6 cycles of VRL, and follow-up CT/PET scan demonstrated complete metabolic and radiological responses. We, therefore, believe that this rash was linked to VRL administration and correlated with response to therapy. Rash has been recognized as a useful surrogate marker with targeted agents such as cetuximab and erlotinib; to the best of our knowledge, this case report describes the first patient with a possible drug rash and its association with a positive outcome. This case report incites interest in further investigation of similar cases to support this observation, since there is a lack of reports of skin rash with VRL therapy.